Strategi Door To Door, Peran Dan Tanggung Jawab Duta Lingkungan Hidup Dalam Meningkatkan Waste Management Di Sekolah Maitreyawira Batam - Rugianto L. (Journal of Sustainable Business Hub, 2020)
This research is to: (1) find out the Door to Door Strategy, (2) find out the Role, (3) find out the Responsibility of the Maitreyawira School Environment Ambassador in improving Waste Management at Batam Maitreyawira School. This type of research is descriptive qualitative, the research that intends to describe phenomena that occur in the location of research using qualitative data analysis. Data collection techniques include interviews, observation and documentation, while data analysis uses qualitative descriptive techniques. The informant's data consisted of teachers and students who were appointed as Ambassadors of the environment at Batam Maitreyawira School. Each teacher is from the kindergarten, elementary, middle, high school and vocational level. Besides that, it also consisted of 6 students from elementary, junior high, high school and vocational schools totaling 29 people, with 7 male and 22 female people. The results of the study stated that the door-to-door strategy of the DLH (Environmental Ambassador) could be applied by conducting field surveys. As for knowing the role of the DLH by applying guidance intensively. To find out the responsibilities of DLH SMW by applying sincerity and making it as duty that is trustworthy and noble.